Bladder dysfunction in distal autonomic neuropathy of acute onset. Issue 8 (August 1985) - Kirby, R S; Fowler, C J; Gosling, J A; Bannister, R
Abstract : A patient with cholinergic dysautonomia and a patient with pandysautonomia have each been investigated for disturbances of bladder and urethral function. Both patients suffered from an inability to develop or sustain a detrusor contraction, while retaining normal bladder sensation. Biopsy specimens of bladder muscle stained for acetylcholinesterase revealed a significant reduction in cholinergic nerves compared with controls; however, the prominent cholinergic subepithelial plexus was strikingly preserved. These findings lend support to the view that acetylcholinesterase-containing nerves in the bladder muscle are motor fibres responsible for detrusor contraction, while those located in the subepithelium are sensory in function. Urethral sphincter electromyography revealed no abnormality of individual motor units, confirming that motor unit integrity in this muscle is dependent upon somatic rather than autonomic innervation. In the patient with pandysautonomia the proximal urethra was incompetent, while in the patient with cholinergic dysautonomia the bladder neck remained closed, as in controls. This suggests that sympathetic rather than parasympathetic efferent activity is necessary for the maintenance of proximal urethral competence.